Malaysia 13th General Election: how the election manifesto and candidates influenced the voters In Penang? - Omar, Muhamad Fuzi; Othman, Muhammad Hanif (2013)
The paper argue that offering comprehensive election manifesto and offering more qualified candidates are the two major factors that determine the outcomes of the 13th general elections. Thus, in order to provide arguments for this assumption, this paper analyzes the election manifesto as the main references. Besides, the study also analyzes the acceptance of the candidates offered by the party especially BN during the election. Third, study then refer mainly to the election results as the main outcome for the elections. The study then shows how the strong and convincing manifesto and qualified candidates as offered by the BN failed to garner the majority supports from the voters towards the party in Penang.